2012
DOI: 10.12659/msm.882721
|View full text |Cite
|
Sign up to set email alerts
|

A review of subclavian steal syndrome with clinical correlation

Abstract: SummarySubclavian ‘steal’ phenomenon is a function of the proximal subclavian artery (SA) steno-occlusive disease, with subsequent retrograde blood flow in the ipsilateral vertebral artery (VA). The symptoms from the compromised vertebrobasilar and brachial blood flows constitute the subclavian steal syndrome (SSS), and include paroxysmal vertigo, drop attacks and/or arm claudication. Once thought to be rare, the emergence of new imaging techniques has drastically improved its diagnosis and prevalence. The syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
142
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(148 citation statements)
references
References 43 publications
2
142
0
4
Order By: Relevance
“…29 Hemodynamic changes in VAs associated with head rotation may also play a role in the subclavian steal syndrome (SSS), which is defined as a group of symptoms that arise from the reversed blood flow in the VA when there is a stenosis in the ipsilateral subclavian artery. 25 The prevalence and impact of this syndrome have been recently reported by Labropoulos et al 19 Peluso et al 27 have reported cases of vertebrobasilar aneurysms in patients with fenestration of the proximal BA and evidence of subarachnoid hemorrhage. The possible vessel compression reported by Sakaguchi et al 31 combined with the geometrical and flowfield changes reported in the present study indicate a possibility of influencing an environment that may favor aneurysmal rapture.…”
Section: Discussionmentioning
confidence: 91%
“…29 Hemodynamic changes in VAs associated with head rotation may also play a role in the subclavian steal syndrome (SSS), which is defined as a group of symptoms that arise from the reversed blood flow in the VA when there is a stenosis in the ipsilateral subclavian artery. 25 The prevalence and impact of this syndrome have been recently reported by Labropoulos et al 19 Peluso et al 27 have reported cases of vertebrobasilar aneurysms in patients with fenestration of the proximal BA and evidence of subarachnoid hemorrhage. The possible vessel compression reported by Sakaguchi et al 31 combined with the geometrical and flowfield changes reported in the present study indicate a possibility of influencing an environment that may favor aneurysmal rapture.…”
Section: Discussionmentioning
confidence: 91%
“…The "subclavian steal syndrome" is rather rare, but can cause ECL due to retrograde blood flow in the vertebral artery associated with proximal ipsilateral subclavian artery stenosis or occlusion (Osiro et al 2012 Evidence-based medicine progress infers the need of new standards in management of a first episode of consciousness loss. Early and successful interventions are conditioned by existence of multidisciplinary protocols and prompt access to specialist care (Beghi et al, 2006;NICE, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The type of waveform on duplex ultrasound of the vertebral arteries corresponds to the severity of the subclavian steal phenomenon (3). The most common cause of subclavian steal syndrome is atherosclerosis (5); other unusual causes include arteriopathy (Takayasu's disease, temporal arteritis) and congenital lesions of the aortic arch or subclavian artery (5,6). Symptoms resulting from subclavian steal syndrome generally include arm claudication, paroxysmal vertigo, syncope, drop attacks, dizziness, diplopia, ataxia and dysarthria (5).…”
Section: Discussionmentioning
confidence: 99%